Digital Marketing Communication Strategy at Gradin Agency in Building Brand Image - Nirwan, Raslika Sharfina; Herdono, Ismojo; Wono, Hilda Yunita (International Journal of Environmental, Sustainability, and Social Science, 2026)
The digital marketing communication strategy plays an important role in the era of rapid technological development. Companies must adapt to maintain consumer interest and drive sales. Many companies compete by promoting their products and brand to ensure consumer recognition. To achieve this, companies employ various digital tools to build brand recognition. This study aims to understand how digital marketing communication strategies shape brand image at Gradin agency. The research employs theories of communication strategy, marketing communication, digital marketing, and brand image. This quasi-qualitative research systematically describes the research object using communication strategy, digital marketing, and brand image theories. The method includes interviews and documentation to enhance data analysis related to organizational communication at Gradin agency. Researchers developed research instruments, including interview guidelines and questions based on research indicators. The result is an innovative digital marketing communication strategy, optimizing website features, creating interactive content on Instagram and TikTok, communicating with consumers through email marketing, and optimizing content and keywords for SEO. These strategies help Gradin create a positive brand image.